2008
DOI: 10.1093/gerona/63.11.1219
|View full text |Cite
|
Sign up to set email alerts
|

Survival After 100 Years of Age: A Multivariate Model of Exceptional Survival in Swedish Centenarians

Abstract: Individual characteristics such as physiological reserve, present health and functional status, as well as chance appear important for centenarian survival. Hereditary factors, social relationships, marital status, and personality did not contribute to survival prediction in this exceptional age group. From a theoretical point of view, our data suggest that, in very old age, stochastic determinants may dominate over programmed factors (e.g., family longevity) in determining survival. More research is needed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 22 publications
4
32
0
Order By: Relevance
“…They reported that measurement of physical and cognitive function, rather than a simple count of comorbid conditions, is a key component for a definition of successful ageing. Similar results were found by Long Life Family and the Framingham studies [57, 58], the Swedish Centenarian study [59], and the Honolulu Heart study [60]. …”
Section: Successful Ageingsupporting
confidence: 87%
“…They reported that measurement of physical and cognitive function, rather than a simple count of comorbid conditions, is a key component for a definition of successful ageing. Similar results were found by Long Life Family and the Framingham studies [57, 58], the Swedish Centenarian study [59], and the Honolulu Heart study [60]. …”
Section: Successful Ageingsupporting
confidence: 87%
“…Moreover, it confirmed the predictive power of good physical ability (self-sufficiency for the basic ADL items), intact cognitive functioning (SMMSE test), positive self-rated health, absence of past myocardial infarction, BMI and hand grip strength over the median for future survival. Therefore, given this increasing importance of the functional status as a predictor of survival, it is worth noting that, at an even more exceptional old age (after age 100), survival is mainly dependent on physiological reserve, physical and cognitive functions, as found in a study on Swedish centenarians (Hagberg and Samuelsson 2008). In spite previous studies showed that poor self-rated health was associated with increased mortality only in women (Nybo et al 2003), our results indicated that "excellent/good" self-reported health might be considered as one of the factors predicting survival in the oldest old, as found in more recent studies on old subjects from Calabria (Montesanto et al 2010) and from Denmark (Dato et al 2012).…”
Section: Discussionmentioning
confidence: 97%
“…In this vein, two reports, one of Japanese centenarians (57) and one of Swedish centenarians (58) focus on the question of survival predictors in this population. In a fascinating study, Arai and colleagues (57) found that a set of novel risk factors linked to adipose–endocrine function and the insulin-like growth factor-1 axis could reliably predict survival in a very old Japanese population.…”
Section: Global Approaches To Understanding Healthy Aging: the Role Omentioning
confidence: 99%